PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LISTENER TEAM TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELSA VIII SMPN 26 SOLOK SELATAN - Susmarni, Susmarni; Harisman, Yulyanti; Suryani, Mulia (Pendidikan Matematika, 2014)
ABSTRACTÂ This research was conducted based on the phenomena showing that the studentsâ understanding on mathematics concept was still low and they had less attention to the teacherâs explanation. This research was designed for revealing whether the mathematics conceptual understanding of the students taught by using Listener Team active learning strategy was better than that of students taught by using conventional learning. This was an experimental research. The population of the research was the students in class VIII of SMPN 26 Solok Selatan registered in Academic Year 2013/2014. By using random sampling technique. The instrument of the research was a post-test. The data collected in this research was analyzed by using t-test. The result of data analysis showed that the value of tcalculated was bigger than ttable. Therefore, it can be concluded that the mathematics conceptual understanding of the students taught by using Listener Team active learning strategy.